FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATWAKTUAN PELAPORAN KEUANGAN TAHUNAN PERUSAHAAN (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar pada Bursa Efek Indonesia Tahun 2012-2013) - Upik Maharani; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
The  aims  of  this  research   to  test  the  company's  annual   financial   reporting timeliness influenced by the effectiveness of the audit committee, the age of the company, Debt  to  Equity  Ratio  (DER),  profitability  and  solvency.  Annual  financial   reporting timeliness is measured  using a dummy variable,  the effectiveness of the audit committee effectiveness is measured using an index developed by Ika and Ghazali (2009), the age of the  company  is  measured  by how  long  the  company  is  listed  in  the  Indonesia  Stock Exchange,   DER  proxied  by  Total  Debt  divided  by  Total  Equity  owned  company, profitability is proxied by the ROA, while solvency is proxied by TDTA (Total Debt to Total Assets).The sample was 624 non-financial companies listed on the Stock Exchange during 2012-2013,  which obtained  by purposive sampling method. To examine the relationship variables of this research, used logistic regression analysis.The results  showed that the effectiveness of the audit committee and profitability have a significant positive effect on the company's annual  financial reporting  timeliness. As for the  age  of the company,  DER, and  solvency show that  these  variables  did not significantly influence the company's annual financial reporting timeliness.